PREVALENCE AND CHARACTERISTICS ASSOCIATED WITH POST– COVID-19 CONDITION AMONG NONHOSPITALIZED ADOLESCENTS AND ADULTS - Akhmedova Nilufar Sharipovna; Ahmadova Marjona Raxmatulloevna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Post-COVID  syndrome  also  known  as  long  COVID  refers  to  symptoms persisting for more than three weeks after the diagnosis of COVID-19. We reviewed the current evidence on post-COVID syndrome, focusing on its clinical manifestations and addressing the challenges for its management in primary healthcare. The incidence of post-COVID syndrome is estimated at 10–35%, while for hospitalized patients it may reach 85%. Fatigue is the most common symptom reported in 17.5–72% of post-COVID cases, followed by residual dyspnea with an incidence ranging from 10–40%. Mental problems, chest pain, and olfactory and gustatory dysfunction may affect up to 26, 22 and 11% of patients, respectively. More than one third of patients with post-COVID syndrome have pre-existing comorbidities, hypertension and diabetes mellitus being  the  most  common.  Beyond  the  prolonged  duration  of  symptoms,  the  scarce published data indicate that most patients with post-COVID syndrome have a good prognosis with no further complications or fatal outcomes reported. Given the clinical spectrum of patients with post-COVID syndrome, most of them will be managed by primary  healthcare  professionals,  in  conjunction  with  pre-existing  or  new  co-morbidities,  which,  in  turn,  may  increase  the  burden  of  COVID-19  on  primary healthcare. In conclusion approximately 10% of patients with COVID-19 may have symptoms  persisting  beyond  three  weeks,  fulfilling  the  criteria  of  post-COVID syndrome.  Primary  healthcare professionals have  a  key  role  in  the  management of patients with post-COVID syndrome. Research is needed to elucidate the pathogenesis, clinical spectrum, and prognosis of post-COVID syndrome.